2013
DOI: 10.1021/jp404791g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tuning of the Closed Shell C–H···F–C Hydrogen Bond

Abstract: The existence of the rare six-membered and intramolecular C-H···F-C hydrogen-bond has been experimentally proven in the gas phase and in the solid state recently. However, the effect of the substituents on this C-H···F-C hydrogen-bond system has never been reported. In view of the importance of this type of C-H···F-C H-bonding whose weak interaction has been found critical in nanotechnology and biological systems, the nine functional groups composed of electron donating and electron withdrawing groups are inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Lectka and co-workers then studied slightly different tricycles 26 (Figure 25) bearing various substituents. 62 Similar to the above study from Lu, Francisco, and Negishi, 59 variations of the X moiety altered the properties of the observed C-H•••F bond. In this system, with the hydrogen bond being so short, the magnitude of the 1h J (H,F) coupling constant (up to 30.7 Hz) correlates with the increased frequency of the C-H bond stretching and therefore with the strength of the interaction.…”
Section: Short Review Syn Thesissupporting
confidence: 67%
See 1 more Smart Citation
“…Lectka and co-workers then studied slightly different tricycles 26 (Figure 25) bearing various substituents. 62 Similar to the above study from Lu, Francisco, and Negishi, 59 variations of the X moiety altered the properties of the observed C-H•••F bond. In this system, with the hydrogen bond being so short, the magnitude of the 1h J (H,F) coupling constant (up to 30.7 Hz) correlates with the increased frequency of the C-H bond stretching and therefore with the strength of the interaction.…”
Section: Short Review Syn Thesissupporting
confidence: 67%
“…In another computational study, Lu, Francisco, Negishi, and co-workers analyzed the six-membered hydrogen bond in model substrate 25 ( Figure 24) bearing a variety of electron-donating and -withdrawing X and Y groups. 59 Analyzing the three X-modified series independently, the authors showed that the C-H•••F hydrogen bond becomes stronger with increasing electron-donating ability of Y substituent, as expected in such a system, and they observed this by measuring an increase in the C-H vibration frequency. Associated with the strengthening of the interaction were a shorter H•••F distance, longer C-F bonds, and shorter C-H bonds.…”
Section: C(sp 3 )-H As Donormentioning
confidence: 78%
“…The structure of 1o in the solid state is best described as the infinitely connected dimer pairs, so we call it as a double belt (whose better pictorial view is highlighted and shown as Fig. S1 in ESI †) in this study, resulting from (1) a vertical Pt⋯Pt interaction with a short distance of 3.590 Å at 295 K (3.579 Å at 250 K), creating a dimer-pair with two bpyPtBr 2 molecular planes facing each other in a head to tail fashion, (2) the fluorinated side chains 17 on bpy running vertically towards the molecular plane of the partner, with two methylene C-H⋯O interactions 18 linking adjacent ponytails within the dimer-pair, (3) two extra methylene C-H⋯Br short contact interactions, also inside the dimer-pair, (4) for connective dimer-pairs, horizontal Br⋯H3-C3 and Br′⋯H4′-C4′ interactions on both the top belt and the bottom belt running antiparallel, and (5) additionally for connective dimer-pairs, two terminal C-F⋯H4-C4 interactions. 17,18 The molecular structure of 1o is shown in Fig.…”
Section: Structural Polymorphismmentioning
confidence: 99%
“…Water interacts with the ionic species via its strong H-bonding capacity as well as charge-dipole interactions. On the other hand, a great deal of recent work has shown that the CH group can serve as a potent proton donor in H-bonds (HBs) in parallel fashion to OH and NH donors [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. CH••X HBs are quite prevalent in nature, in biological [27][28][29][30][31][32][33][34][35] as well as chemical [36][37][38][39][40][41][42][43][44] contexts.…”
Section: Introductionmentioning
confidence: 99%